Pengaruh Ekstrak Daun Binahong (Anredera Cordifolia (Ten.) Steenis) Terhadap Jumlah Fibroblas pada Ulkus Traumatikus Tikus Putih Diabetes Melitus - Hidayat, Lukman Hakim; Maria, Ervina (Fakultas Kedokteran Gigi UB, 2025)
Introduction: Diabetes mellitus is a condition of hyperglycemia that occurs due to abnormal insulin secretion. This condition causes an increase in Reactive Oxygen Species, thereby reducing the production of growth factors such as TGF-β for fibroblast synthesis. Traumatic ulcers are ulcerative lesions characterized by the loss of the epithelial layer due to trauma. Binahong leaves (Anredera cordifolia (Ten.) Steenis) contain flavonoids and saponins that can accelerate wound healing. Objectives: This study aims to analyze the effect of binahong leaf extract gel (Anredera cordifolia (Ten.) Steenis) on the number of fibroblast cells in the healing of traumatic ulcers in white rats with diabetes mellitus. Methods: This study used a true experimental design in vivo with 32 male Wistar rats divided into 4 groups with 2 time series. The variable being studied is the average number of fibroblast cells observed on the 5th and 7th days. The doses of binahong leaf extract gel (Anredera cordifolia (Ten.) Steenis) used were 10% and 20%. Result: The group given 10% and 20% binahong leaf extract gel showed an increase in the number of fibroblasts compared to the other control groups. This difference is significant compared to the control group based on the Post-hoc Tuckey test with a p-value <0.05. Conclusion: The gel of binahong leaf extract (Anredera cordifolia (Ten.) Steenis) significantly increases the number of fibroblast cells in the healing of traumatic ulcers of the labial mucosa in white rats (Rattus norvegicus) Wistar strain induced by diabetes mellitus, and a concentration of 10% is quite effective for the healing of traumatic ulcers. Keywords: Binahong leaf, diabetes melitus, fibroblast, traumatic ulcers, wound healing.